2018
DOI: 10.1016/j.dci.2017.11.007
|View full text |Cite
|
Sign up to set email alerts
|

3,4-Dihydroxyphenylacetaldehyde synthase and cuticle formation in insects

Abstract: Cuticle is the most important structure that protects mosquitoes and other insect species from adverse environmental conditions and infections of microorganism. The physiology and biochemistry of insect cuticle formation have been studied for many years and our understanding of cuticle formation and hardening has increased considerably. This is especially true for flexible cuticle. The recent discovery of a novel enzyme that catalyzes the production of 3,4-dihydroxyphenylacetaldehyde (DOPAL) in insects provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 88 publications
(99 reference statements)
2
17
0
Order By: Relevance
“…In Papaveraceae, on the other hand, we noticed a His-to-Leu substitution in the previously reported P. somniferum tyrosine decarboxylase 1 (PsTyDC1) (8) and a His-to-Tyr substitution in another Papaver bracteatum AAAD homolog. While the small-loop histidine is typically conserved among type II PLP decarboxylases and the broader type I aspartate aminotransferases, the same His-to-Asn substitution was previously observed in select insect AAAD proteins involved in 3,4-dihydroxyphenylacetaldehyde production necessary for insect soft cuticle formation (37,38). These sequence observations together with the proposed catalytic role of the small-loop histidine implicate that AAADs that carry substitutions at this highly conserved residue position may contain alternative enzymatic functions.…”
Section: Convergent Evolution Of Two Mechanistic Classes Of Aasssupporting
confidence: 55%
“…In Papaveraceae, on the other hand, we noticed a His-to-Leu substitution in the previously reported P. somniferum tyrosine decarboxylase 1 (PsTyDC1) (8) and a His-to-Tyr substitution in another Papaver bracteatum AAAD homolog. While the small-loop histidine is typically conserved among type II PLP decarboxylases and the broader type I aspartate aminotransferases, the same His-to-Asn substitution was previously observed in select insect AAAD proteins involved in 3,4-dihydroxyphenylacetaldehyde production necessary for insect soft cuticle formation (37,38). These sequence observations together with the proposed catalytic role of the small-loop histidine implicate that AAADs that carry substitutions at this highly conserved residue position may contain alternative enzymatic functions.…”
Section: Convergent Evolution Of Two Mechanistic Classes Of Aasssupporting
confidence: 55%
“…The insect cuticle undergoes sclerotization, melanization and other physiological processes to play a protective role [8, 10, 11]. DOPAL synthase can catalyze the reaction from L-dopa to DOPAL, which can interact with free amino acids of CPs and directly participate in surface protein cross-linking [1517]. However, there is no known biological effect of DOPAL in the postembryonic development of mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
“…Structural and biochemical comparisons between DOPAL synthase and DDC in Drosophila identified that the key active site residue, Asn192, in insect DOPAL synthase can be used to distinguish all available insect DOPAL synthases from DDC sequences [15]. DOPAL has a high biological activity, which is directly linked to the CPs cross-linking through interaction of free amino acid groups on the CPs [11, 16, 17]. Early studies reported that DOPAL synthase-like protein, alpha methyldopa resistant (AMD-r), in Drosophila is resistant to the toxic compound, AMD.…”
Section: Introductionmentioning
confidence: 99%
“…The product of this enzyme, DHPAA, is hypothesized to be important in uncolored, flexible cuticle formation in insects, perhaps through aiding crosslinking of cuticular proteins (Fig. 6B) [55,56]. The Drosophila gene had been previously designated α‐methyldopa hypersensitive (amd) gene, based on observed sensitivity to AMD when the gene was mutated [57‐60].…”
Section: Amino Acid Aldehyde Synthasesmentioning
confidence: 99%